Alzheimer's disease research: a network science approach - Pestana, M. H.; Sobral, M. R. (International Journal of Multivariate Data Analysis, 2018)
A limit number of studies have applied bibliometric visualisation to explore the network structure of Alzheimer’s Disease (AD). This paper uses CiteSpace, Carrot and VOSviewer to analyse and visualise the intellectual structure of AD, characterizing, quantitatively and qualitatively, the global scientific outputs, and identifying their trends. The 9,753 articles obtained from the science citation index expanded database (SCI-E), from Web-of-Science, were analysed. The publication data is analysed computationally to identify publication patterns, a rate of growth of publications, types of authorship collaboration, the most productive authors, countries, institutions, journals, keywords, the citation and keyword patterns, the hotspots and the areas of research on the AD. The paper presents a detailed analytical mapping of AD research and charts the progress of discipline with various useful parameters. The authors expect to contribute to the theory, supplying researchers with new tools and enabling practitioners to improve their knowledge about the AD evolution and trends.